Dancing Waters (Benjamin New Co., Ltd.)
Dancing Waters: Sponsored by the Canadian Westinghouse Company Limited. The world's largest fountain, 210 feet long. Vivid lighting effects are achieved by 87 powerful floodlights, each producing a number of distinct colour patterns.